An investigation of sensory integration across the autistic spectrum using multisensory illusions - Masood, Salik (2022)
In order to have a comprehensible representation of scenes and events, the human brain must combine information from different sensory sources. Integration of visual, tactile, and proprioceptive information is considered vital to this process as it underpins the subjective sense of self and body ownership; which has been linked to the development of social processes such as empathy and imitation. This issue has been investigated using sensory illusions and suggests that individuals with autism are less prone to multimodal illusions due to atypical sensory integration, i.e. they tend to rely on a single sensory source more, rather than integrating concurrent sources of information (i.e. over-reliance on proprioception). Studies that have measured illusion susceptibility and ownership, especially in regards to body ownership have provided mixed results. Therefore, it is important to understand and advance our knowledge on illusion susceptibility using sensory illusions.